Associations of lung function impairment and biological aging with mortality and cardiovascular disease incidence: findings from UK biobank participants - Jiali Chen; Cheng Wang; Pengyu Duan; Yonghong Bi; Yao Meng; Weiyu Feng; Zhehao Jin; Hangbing Li; Huihui Wang; Xiaoyan Li; Kun Zuo; Xiangcheng Zhao; et al. (Frontiers in Public Health, 2025)
BackgroundLung function impairment, including preserved ratio impaired spirometry (PRISm) and airflow limitation (AL), is associated with increased risks of mortality and cardiovascular disease; however, the underlying biological mechanisms remain poorly understood. This study aimed to investigate the mediating role of biological aging, as well as the interactions and joint effects of lung function impairment and biological aging on adverse health outcomes.MethodsA total of 349,456 UK Biobank participants (aged 40–69 years) were categorized into normal, PRISm, and AL groups based on baseline spirometric measurements. Biological aging was assessed using phenotypic age acceleration (PhenoAgeAccel) and frailty phenotype. PhenoAgeAccel was calculated using algorithms based on clinical biomarkers, and frailty was evaluated according to five established criteria. Cox proportional hazards models were used to assess the risks of all-cause mortality and CVD (including coronary artery disease, heart failure, and ischemic stroke). Mediation and interaction analyses further examined the associations between lung function impairment, biological aging, and adverse health outcomes.ResultsOver an average follow-up of 13.8–14.4 years, 28,059 deaths and 34,863 incident CVD cases were recorded. PhenoAgeAccel mediated 12.8–16.2% of the association between lung function impairment and mortality, compared to 7.0–12.0% for frailty. For CVD, the mediation proportions were 8.5–15.9% (PhenoAgeAccel) and 7.4–8.6% (frailty). Significant multiplicative and additive interactions were found between lung function impairment and biological aging, especially for mortality risk. The joint analysis revealed that participants with both impaired lung function and accelerated biological aging had the highest mortality and CVD risks.ConclusionBiological aging partially mediates the associations between lung function impairment and adverse outcomes, exhibiting synergistic interactions with impaired lung function. Thus, therapies targeting biological aging may complement conventional lung function promotion in reducing health disparities among aging populations.